Three-dimensional interconnected cobalt sulfide foam: Controllable synthesis and application in supercapacitor - Liu, Ye; Guo, Shoujing; Zhang, Wei; Kong, Wei; Wang, Zhongde; Yan, Wenjun; Fan, Huiling; Hao, Xiaogang; Guan, Guoqing (Electrochimica Acta, 2019)
Transition metal sulfides have been considered as the promising electroactive materials for the supercapacitors with high specific capacitances. Herein, cobalt sulfide foam (CSF) with three-dimensional (3D) porous hierarchical structure was controllably synthesized on the electrode by the facile electrochemical reduction of elemental sulfur in the precursor of sulfur incorporated polypyrrole (S/PPy) composite with a electrochemical reduction method followed with in-situ reacting with Co2+ ions in the electrolyte, and used for high-performance supercapacitors. Since such a CSF material provided smooth ion diffusion pathways for the fast ion transfer between electrode and electrolyte and simultaneously the anchoring of conductive PPy to the cross-linked cobalt sulfide (CoS) nanosheets enabled good electrical contact between the current collector and the active material for the fast electron transfer. By synergetic combination of these advantages, the optimum electrode delivered exceptional rate capability (84.8% capacity retention from 1 to 20 mA cm−2) and excellent cycling stability (86.8% capacity retention after 10000 cycles). An asymmetric supercapacitor assembled with the CSF as the positive electrode and activated carbon as the negative electrode displayed outstanding electrochemical performance. It is expected to provide a green and simple method for the preparation of transition metal sulfide-based electrodes for the practical energy storage. [Display omitted] •Cobalt sulfide foam (CSF) is fabricated by electrochemical reduction of sulfur.•CSF with 3D hierarchical structure provides unobstructed ion diffusion pathways.•PPy facilitates the electronic transportation between CoS and carbon paper.•Chemical bonding between PPy and CoS enables cycling stability of electrode.